Psychological Well-being of Students in a Diverse University Environment - L.V. Fedina; G.V. Kukhterina; G.G. Saitgalieva; Т.V. Semenovskikh; E.A. Soloveva (Moscow State University of Psychology and Education, 2023)
The high diversity of the student sets the requirements for redundancy of conditions and environments in a modern university. Unified models of formation and standards do not allow us to see the individuality of students and solve the problems of social inclusion. Professional training should take into account the satisfaction and well-being of students. We are exploring the indicators of psychological well-being and constructive behavioral activity among students studying in a diversity university environment. The empirical basis of the study was Tyumen State University, where the model of individual educational trajectories is implemented. The principles of individualization define the heterogeneity of the university environment at the educational, communicative and organizational levels. The study involved 537 students in the period from 2019 to 2023. The results allowed us to confirm that the diversity environment of the university ambiguously mediates indicators of psychological well-being. Students studying in changing and diverse environment give more importance to a personal growth and personal goals than those who study in the traditional bachelor's model. However, they are less open, not inclined to maintain trusting relationships, less autonomous in forming their own opinions and decisions. In a situation of forced isolation (COVID-19), the psychological well-being of students decreased, which may be due to insufficiently accumulated interpersonal relations during full-time study.